Psychological interpretations of the book of Jonah - Heerden, Schalk Willem van (Old Testament essays, 2003)
This article focuses on interpretations of the book of Jonah that have been done from a psychological perspective. Apart from cursory characterisations of the behaviour and personality of Jonah in psychological terms, some comprehensive analyses of the book as a whole have been done within the framework of particular psychological theories. Interpretations which were informed by a Jungian framework receive special attention. The final section deals with the psychological impact - especially the cathartic effects - of reading literature like the Jonah narrative.